2017
DOI: 10.1093/cercor/bhx321
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation Structure in the Macaque Dorsolateral, But not Orbital or Polar, Prefrontal Cortex Predicts Response-Coding Strength in a Visually Cued Strategy Task

Abstract: Abstract In previous work, we studied the activity of neurons in the dorsolateral (PFdl), orbital (PFo), and polar (PFp) prefrontal cortex while monkeys performed a strategy task with 2 spatial goals. A cue instructed 1 of 2 strategies in each trial: stay with the previous goal or shift to the alternative goal. Each trial started with a fixation period, followed by a cue. Subsequently, a delay period was followed by a “go” signal that instructed the monkeys to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 60 publications
9
50
1
Order By: Relevance
“… was mostly driven by between-region differences and was not a property of individual neural response. In addition, our findings contradict a few recent studies showing that intrinsic timescales based on autocorrelation can predict encoding of task-relevant signals in some cortical areas(Cavanagh et al,, 2016;Cavanagh et al, 2018;Fascianelli et al, 2019;Nishida et al, 2014;Wasmuht et al, 2018). This could be due to differences in the experimental paradigms, methods for estimations of intrinsic timescales, or both, and could simply reflect reporting bias considering the large number of studies that have examined the decay in autocorrelation of neural response.…”
contrasting
confidence: 98%
See 1 more Smart Citation
“… was mostly driven by between-region differences and was not a property of individual neural response. In addition, our findings contradict a few recent studies showing that intrinsic timescales based on autocorrelation can predict encoding of task-relevant signals in some cortical areas(Cavanagh et al,, 2016;Cavanagh et al, 2018;Fascianelli et al, 2019;Nishida et al, 2014;Wasmuht et al, 2018). This could be due to differences in the experimental paradigms, methods for estimations of intrinsic timescales, or both, and could simply reflect reporting bias considering the large number of studies that have examined the decay in autocorrelation of neural response.…”
contrasting
confidence: 98%
“…A few recent studies have shown that intrinsic timescales during the fixation period-presumably before strong task-relevant signals emerge in the cortical activity --can predict encoding of task-relevant signals later in the trial for some but not all cortical areas. This includes the encoding of chosen value during value-guided decision making (Cavanagh et al, 2016), persistent activity during working-memory tasks (Nishida et al, 2014;Cavanagh et al, 2018;Wasmuht et al, 2018), and activity related to upcoming behavioral responses during a visually-cued strategy task (Fascianelli et al, 2019;Cirillo et al, 2018). However, in all these studies, the decay rate of autocorrelation in the firing response of individual neurons during one epoch of the task (fixation period) is compared with encoding of task-relevant signals in other epochs of the task.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) found that neurons with delay activity specialized to maintain information presented slow intrinsic timescales. Similar results were later described in the PFC (Cavanagh et al., 2016, Fascianelli et al., 2017), but with differences between the PF subdivisions between the two studies, which could be explained by task differences. Fascianelli et al.…”
Section: Introductionsupporting
confidence: 86%
“…Other studies, using another approach, instead of focusing on the heterogeneity of timescales across areas, examined differences in intrinsic timescales across neurons within the same cortical area (Nishida et al., 2014, Cavanagh et al., 2016, Fascianelli et al., 2017), to address whether distinct functional classes of neurons might also show timescale differences based on their specific functions.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent activity has been reported in multiple cortical areas with differing functional properties. The intrinsic timescales of neural activity have been found to vary between cortical regions 18 in a manner that predicts the functional properties of persistent activity across cortical regions 19 , 20 . “In addition to prefrontal activity, sensory areas have been found to encode stimulus information across a delay period in the form of post-stimulatory activity.…”
Section: Introductionmentioning
confidence: 99%